2012
DOI: 10.1038/gim.2011.10
|View full text |Cite
|
Sign up to set email alerts
|

IRB perspectives on the return of individual results from genomic research

Abstract: Purpose Return of individual research results from genomic studies is a hotly debated ethical issue in genomic research. However, the perspective of key stakeholders—Institutional Review Board (IRB) reviewers—has been missing from this dialogue. This study explores the positions and experiences of IRB members and staff regarding this issue. Methods In depth interviews with 31 IRB professionals at six sites across the United States. Results IRB professionals agreed that research results should be returned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 30 publications
0
65
0
Order By: Relevance
“…Currently, there exist very heterogeneous research ethics guidelines on the return of results to research participants, which vary between countries and even between institutions [37,38]. To some extent, the issue of return of results is addressed by ethical guidelines that recommend reporting incidental findings that are clinically relevant [39].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there exist very heterogeneous research ethics guidelines on the return of results to research participants, which vary between countries and even between institutions [37,38]. To some extent, the issue of return of results is addressed by ethical guidelines that recommend reporting incidental findings that are clinically relevant [39].…”
Section: Discussionmentioning
confidence: 99%
“…50 Also, REC professionals supported the return of incidental findings if the results were valid, clinically significant, treatable or preventable and if the participants wanted to receive them. 51 Regarding the reasons in favor of receiving incidental findings, patients and the public had similar perspectives, namely that the return of incidental findings would allow them to make decisions in family planning and take preventive actions to avoid certain diseases. 43,52 In addition, empowerment, respect for persons, a better public recognition of research and a feeling of control were expressed as arguments for the return of incidental findings.…”
Section: Professionals/public N=2mentioning
confidence: 99%
“…33,50 Professionals shared the concerns about potential emotional and psychological harm to the patients in several quantitative and qualitative studies. 51,[53][54][55][56] Some felt that this could in turn lead to a loss of public trust in research institutions. 54 The most prominent concern of professionals was the complexity of the results, the uncertainty in their interpretation and concerns about the quality of information, including validity and clinical utility of genomic findings.…”
Section: Professionals/public N=2mentioning
confidence: 99%
“…In addition, individual results may be offered results if other conditions are met (National Heart Lung Blood Institute working group et al 2010). Since then, studies have identified support for disclosing personal genomic results from genomic study participants (Allen et al 2014;Bollinger et al 2012;Halverson and Ross 2012;Overby et al 2015;Trinidad et al 2015), researchers (Appelbaum et al 2015;Meacham et al 2010), IRB committee members (Beskow and O'Rourke 2015;Dressler et al 2012), ethicists and lawyers (Burke et al 2014;Evans 2014;Thorogood et al 2014;Wolf et al 2015), and two genomics research networks ). In addition, NHLBI (2010) recommended that Binvestigators conducting research with identifiable communities should engage the community on the return of aggregate and/or individual research results^, and other researchers concurred (Lemke et al 2012;Marsh et al 2013;Overby et al 2015;Trinidad et al 2015).…”
Section: Discussionmentioning
confidence: 99%